Implementation of Exemplary Methods in Improving the Akhlakul Karimah Character of Students at MTS Al-Furqon Klari Karawang - Ulfah Fauziyah; Akil; Ahmad Junaedi Sitika (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research is motivated by the moral problems of adolescents in the era of globalization. So the role of parents, teachers, as role models for children/students in strengthening morals is very important. The aim of the research was to find out the implementation of the exemplary method in strengthening students' moral values. This research uses a qualitative method with a descriptive type. Research data collection methods used are interviews, observation, and documentation. So the results are 1) How is the implementation of the exemplary method in improving the moral character of students a) the application of discipline to existing programs in schools; b) set a good example for students; c) give attention to students. 2) Supporting factors (a) various activities between teachers and students; (b) coordination with other teachers; (c) giving advice to students. 3) Inhibiting factors (a) internal factors, namely students doing things that are not disciplined and do not obey the rules; (b) external factors, namely the influence of the surrounding environment which is not good (c) the various characteristics and characteristics of students. (4) The solution is (a) follow the rules stated in the school; (b) teachers work together with parents, so that students are kept under surveillance from an environment that influences bad morals; (c) teachers and parents work together in instilling good morals or akhlakul karimah